2021
DOI: 10.1016/j.joca.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic osteoarthritis – relation of diabetes and cardiovascular disease with knee osteoarthritis

Abstract: Objective: There is an interest in identifying a metabolic OA phenotype. We therefore assessed the relation of diabetes and cardiovascular disease to prevalent and incident radiographic (ROA) and symptomatic knee osteoarthritis (SxOA). Design: In two large cohort studies of individuals with or at risk for knee OA, the Multicenter Osteoarthritis Study (MOST) and Osteoarthritis Initiative (OAI), participants self-reported diabetes and cardiovascular disease (CVD) at baseline. We assessed the relation of baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Epidemiological studies show a higher prevalence of OA (radiographic and symptomatic) in patients with type 2 diabetes mellitus (T2DM) and a higher rate of arthroplasty 142,143 , with a meta-analysis reporting a higher risk of OA development in patients with T2DM than in those without T2DM (OR 1.46; 95% CI 1.08-1.96; P = 0.01) 144 . Although some studies neither confirmed these findings after adjustment for BMI 145,146 nor detected an association between T2DM and prevalence or incidence of OA 147,148 , some of the studies included in the meta-analysis reported the same increased risk after BMI adjustment, suggesting that T2DM is an independent risk factor for OA development 143 . For example, ultrasonography-detected synovitis and effusion were higher in patients with T2DM and end-stage knee OA who underwent arthroplasty than in those without T2DM, independent of patient BMI 143 .…”
Section: Obesity and T2dmmentioning
confidence: 92%
“…Epidemiological studies show a higher prevalence of OA (radiographic and symptomatic) in patients with type 2 diabetes mellitus (T2DM) and a higher rate of arthroplasty 142,143 , with a meta-analysis reporting a higher risk of OA development in patients with T2DM than in those without T2DM (OR 1.46; 95% CI 1.08-1.96; P = 0.01) 144 . Although some studies neither confirmed these findings after adjustment for BMI 145,146 nor detected an association between T2DM and prevalence or incidence of OA 147,148 , some of the studies included in the meta-analysis reported the same increased risk after BMI adjustment, suggesting that T2DM is an independent risk factor for OA development 143 . For example, ultrasonography-detected synovitis and effusion were higher in patients with T2DM and end-stage knee OA who underwent arthroplasty than in those without T2DM, independent of patient BMI 143 .…”
Section: Obesity and T2dmmentioning
confidence: 92%
“…It is expected that by 2030, 20% of adults will have developed OA in Western Europe and North America [ 3 ], which imposes the morbidity and economic burdens on patients, their families and the society [ 4 ]. Notably, recent studies have also showed robust evidence that OA is a significant risk factor for cardiovascular diseases (CVD) and suggested that patients with OA are twice as likely to develop ischemic heart disease and heart failure which increase mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…KOA is the primary type of meniscus, with high risk of disability, and the incidence in female is higher than that in male [7]. In traditional Chinese medicine, it seems almost inevitable that the morbidity will further increase, with the aging of population and the increasing numbers of obesity [8][9][10]. Conventional treatment for KOA is based on medications such as glucocorticoids and nonsteroidal anti-inflammatory drugs (NSAIDs), and surgery would be considered for severe cases, with a cost unaffordable for many patients [11].…”
Section: Introductionmentioning
confidence: 99%